PENGARUH MULTIPLE LARGE OWNERSHIP STRUCTURE DAN AKTIVITAS KOMITE AUDIT TERHADAP BIAYA AUDIT - Vanda Ayu Cahyaningtyas; Herry Laksito (Diponegoro Journal of Accounting, 2019)
The objective of this study is to examine the effect of multiple large ownership structure and audit committee activity as independent variable against audit fees as a dependent variable. This study refers to the research conducted by Adelopo (2007) in the United Kingdom with some modification to the control variable and the sum of population as a research’s sample. The population in this study is all non-financial companies listed on the Indonesia Stock Exchange in 2017. The method used is purposive sampling. The number of samples that meet the requirements for the study is amounted to 159 companies. Multiple regression were used to test both hypotheses in the study. From the two research hypotheses, the result of the first hypothesis indicate that multiple large ownership structure do not have significant negative effect on audit fees. This is due to the fact that the owners of the company’s stock block in Indonesia tends to be less than four, so that it is classified as a diffused firms. Whereas in the second hypothesis, the audit committee activity have a significant positive effect on the audit fees.